MAKING MORE ACTIVE THE SECURITIES MARKET AND MECHANISMS OF STATE PARTICIPATION - S. D. Cholbaeva (Финансы: теория и практика)
The scope and methods of attracting financial resources in different countries have specific features; however at the current stage of the global financial market development, a significant part of financial resources is attracted by issuing securities. The securities market in the Kyrgyz Republic emerged in the time of the privatization of state enterprises in different economic sectors. The first issuers appeared; they were joint-stock companies, investors and professional players of the securities market. It is known that dynamically developing economy is based on the development of the financial market of the country. The volume of the stock market shows not only its development at the moment, but also it is a good base to draw conclusions about all the economy in general. The stock market is often called a “mirror of the economy.” The analysis shows that unlike Russia, the Kyrgyz Republic has no experience in making transactions using financial derivatives on the domestic and foreign markets as well as in hedging price risks on the currency, oil or stock markets. The main reason for the lag is the lack of legislative framework for markets of derivative financial instruments.